NCSA 2022 John F. Schnable Teaching Address: Teaching in the Age of Accountability: What's a Sociologist to Do?. Issue 4 (2nd October 2022) - Senter, Mary Scheuer
ABSTRACT: The pandemic has exacerbated the dilemmas facing college students and their institutions of higher education, and the pressures on institutions to be accountable to multiple stakeholders have, if anything, increased. No one is opposed to accountability in principle. The issue, rather, is who determines what constitutes academic quality and the key dimensions of student success. A substantial literature now exists highlighting the problems that accrue when neoliberal thinking gains ascendancy in higher education. What is not stressed enough in these discussions are the implications of the neoliberal audit mentality on pedagogy itself – on how we teach. I will discuss the negative impact on teaching of three accountability systems that are widely institutionalized on college campuses – the student evaluation of teaching at the end of the semester, the assessment of student learning in the major, and program review of the major or academic program. Further, I will outline ways that we as sociologists might act as individual faculty members, as members of departments, or as members of larger professional organizations to resist or mitigate those pressures. As sociologists, we should be well positioned to see beyond the individual course or career and to argue for the collective with a reality sui generis .